PO 8278 Building capacity in conducting clinical research in a virtual setting: experiences from the east african consortium for clinical research (EACCR2). (24th April 2019) - Nyanzi-Kabuye, Emily; Kaleebu, Pontiano; Kikaire, Benard; Mmbaga, Blandina T; Mfinanga, Godfrey S; Peshu, Norbert; Mukhtar, Maowia
Abstract : Background: EACCR2 is an EDCTP-funded, Eastern African-led network established in May 2009, with 23 regional partners from Ehtiopia, Kenya, Sudan, Tanzania, and Uganda, and 8 northern partners from Germany, Netherlands, Norway, Sweden and United Kingdom. The objective is to strengthen capacity to conduct health research to international standards with specific focus on clinical trials on poverty-relevant diseases such as HIV, TB, malaria and neglected infectious diseases. EACCR2 optimises the use of shared research infrastructures and other regional capacity building resources and opportunities. Activities: The activities of the network are implemented in five work packages cutting across 'nodes' in different countries. Capacity building programmes and studies funded by EDCTP are implemented by coordinators at the disease nodes. The Uganda Virus Research Institute (UVRI) hosts the secretariat of the consortium of five nodes located in the following institutions: Malaria Node in Kilifi-Kenya Medical Research Institute Wellcome Trust, Tanzania; Training Node in Kilimanjaro Clinical Research Institute, Tanzania; Tuberculosis Node at the National Institute of Medical Research- Muhimbili, Tanzania; the Neglected and Re-Emerging Tropical Diseases Node at the University of Khartoum, Sudan; and the HIV Node at UVRI, Uganda. Coordinators form the project implementation committee which meets via skype or teleconference every quarter to assess progress, share best practice and challenges of the network. Scientific and annual meetings are arranged every year in one of the implementing institutions. During such meetings, students, the nodes and steering committee also meet to minimise travel costs while helping teams to network. EACCR2 learns from the experiences, best practice and challenges of EACCR1 while implementing its current activities. Careful planning and consensus building from all partners has been the driving force to build and implement activities of this virtual network. EACCR2 also works closely with other EDCTP Networks of Excellence, i.e. in Central Africa (CANTAM), West Africa (WANETAM), and Southern Africa (TESA).